Desempenho forrageiro de consorciações de cultivares de centeio de diferentes ciclos de produção - Zeni, Manuele (2020)
Seasonality in forage production is a frequent problem in southern Brazil, causing the fall and spring emptiness that impact forage scarcity and reflect in lower profitability in cattle. In this scenario, intercropping of rye cultivars of different cycles is a promising management alternative to minimize the effects of forage deficit. The objective of this work was to evaluate the intercropping of rye cultivars of different production cycles, their forage performance and precocity in relation to the isolated cultivation of double purpose wheat and black oats. The experiment was conducted in the experimental area of Embrapa Wheat, in Coxilha-RS, in 2018, consisting of 10 treatments, T1 = BRS Progresso (rye), T2 = BRS Serrano (rye), T3 = Temprano (rye), T4 = (T1 + T2), T5 = (T1 + T3), T6 = (T2 + T3), T7 = (T1 + T2 + T3), T8 = Embrapa 139 Neblina (black oats), T9 = BRS Pastoreio (double purpose wheat), T10 = BRS Tarumã (double purpose wheat), in a randomized complete design with four replications. The treatments were evaluated for biomass production, leaf blade percentage and nutritive value in each cut. Data were among to analysis of variance and compared by Tukey test at 5% probability significant. Interactions treatments were observed in most cuttings as forage production, daily accumulation rate, leaf blade percentage, neutral detergent fiber, acid detergent fiber and crude protein. In conclusion, the results suggest that rye intercrops with long-cycle cultivars and their isolated cultivation have potential for biomass production with bigger number of cuts (eight to nine). The treatments have high nutritive value, with little variations in the contents along the cuts. The intercropping of the same species used in this study represents an alternative management with rye, as it provides the early supply of fodder (anticipation of fourteen days in fall in relation to wheat) with adequate nutritive value for a longer period period (thirteen more days in compared to wheat), so we should indicate these cultivars for animal feed in South Brazilian conditions